Automation of 6 wheels robot (HOBO L3A1 robot) - Norfadilah, Che Yusoff (2012)
The project is about to design a system which enables the 6 wheel robots named HOBO L3A1 ATM automated. A joystick acts an input to the system which embedded on board by interfacing with microcontroller and must be programmed according to expected result to make the robot in functions. The motor speed direction is controlled by developing H-bridge circuits which interface with microcontroller. The robot consists of 6 wheels of different motors that controlled the robot wheels. The overall robot chassis had finished which was designed with motor controls that driven by independent motor, thus the HOBO ATM robot conveniently switch its locomotion modes according to theoperational. This project should be done in accordance with planning requirements. A microcontroller Arduino AtMega1280/2560 was needed in order to achieve the objectives of the project. An appropriate command need to transfer to the microcontroller. The embedded control system is not done yet, so a control system needs to be established to make the robot automated and functioned as well. The method for this project is designing a schematic diagram of circuit then implemented onto board. The microcontroller was programmed according to desired output. At the end of project,it was expected that the robot wheels can automate after the joystick (input) is controlled.